Weak anion modified monolithic column
By connecting branopenaminels or bellinnamine or uncleamine groups in the inner surface of the inner surface of the channel and the inner surface of the channel of epoxy resin, it is prepared for materials with specific adsorption capacity, and the existing overall column is separated from nucleic acid material separation. The lack of enrichment has achieved high -efficiency and stable nucleic acid material enrichment and separation.
Patent Information
- Application Number
- CN202411449268.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-10
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
AI Technical Summary
The existing monolithic column materials have problems such as low yield, poor stability, inconsistent linear amplification and complex process control in terms of separation and enrichment of nucleic acid substances. The temperature control of the curing and forming process is complex and the cycle is long, resulting in relatively high costs. high.
Epoxy resin base column materials are used to improve the specific adsorption capacity of nucleic acid substances by connecting branched orotic or uncleamine groups in the inner surface of the hole and channel. This material is prepared by the modified steps of hydroxidization, epoxy, and weak yin ions to retain the adsorption performance and liquidity characteristics of epoxy resin materials.
Realize the efficient enrichment and separation of nucleic acid substances, improve the income and stability, simplify process control, reduce costs, and maintain the characteristics of high flow rate and low column pressure.
Smart Images

Figure BDA0005088597720000051 
Figure BDA0005088597720000052 
Figure BDA0005088597720000061
Abstract
Description
Technical Field
[0001] The present invention relates to a monolithic column material, and more specifically, to a monolithic column material for nucleic acid enrichment and separation. Background Art
[0002] At present, the separation and purification of biomolecules are basically achieved by modifying the surface ligands of chromatographic microsphere media to achieve separation and purification of different functions, so as to obtain relatively pure molecules as medicines, diagnostic reagents, biochemical process raw materials, food, cosmetic additives, etc. However, microsphere media as stationary phases have the following disadvantages: 1) The pore distribution is relatively small, and the separation ability for biomolecules with large molecular weight is poor; 2) The diffusion effect of chromatographic microspheres is obvious, and a long retention time is required to fully diffuse to the theoretical specific surface area of the microspheres, which takes longer for biomolecules; 3) The working pressure of the chromatographic column filled with microspheres is high, which is not conducive to the efficient operation of the system.
[0003] Monolith technology is a new generation of chromatographic stationary phase developed in recent years. It currently has obvious advantages over traditional porous microsphere filling media in the rapid separation and purification of biomacromolecules. The monolith consists of a whole block of highly connected pipes, and the fluid flows in the evenly distributed pipes. The monolith matrix is composed of polymers, and the average diameter of its internal pipes is 2μm. Inside the monolith, each pipe is connected to dozens of other pipes. The high connectivity of the pipes helps to evenly distribute the fluid, reduce the operating pressure, and achieve high flow rate and low column pressure.
[0004] At present, the materials of the monolithic column are polymethacrylate polymers or polystyrene polymers. They currently have many commercially successful products on the market, which are relatively successful monolithic column solutions. However, polymethacrylate polymers and polystyrene polymers also have the following problems: 1) The molding temperature is high. When preparing larger size blocks, the process control is complicated due to the thermal effect, the distribution uniformity of the cut channels is poor, and the pore size double distribution phenomenon may occur. In addition, the curing molding is generally at 60-80°C, the time is 12-24 hours, and the cycle is long; 2) After curing molding, the hydrophobicity is strong. In the process of biomacromolecule purification, the non-specific adsorption phenomenon is more obvious. Generally, hydrophilic modification (such as using hydroxyl-rich molecules) is required to reduce the problem of non-specific adsorption; 3) When solidified into a larger pore size, due to its poor toughness, it is easy to be damaged, affecting the use effect. These are the technical problems that monolithic columns will encounter when facing the enrichment and separation of biomacromolecules, and they are also the technical problems that the present invention wants to solve.
[0005] CN202211600949.6 discloses a chromatography material based on epoxy resin, which has uniform internal structure, good preparation reproducibility, high toughness, modifiable functional ligands and high hydrophilicity. CN113145088A discloses a hydrophilic monolithic material and its preparation and application, wherein the monomer triglycidylisocyanurate (TGIC) and 1,4,7,10-tetraazacyclododecane (1,4,7,10-Tetraazacyclododecane, cyclen) are ultrasonically dissolved in an organic solvent, and then an epoxy-amine ring-opening polymerization reaction is carried out under heating conditions to form a monolithic material. Since epoxy reacts with amines to generate a large amount of hydroxyl groups, the monolithic material obtained has good hydrophilicity. EP2485836A1 discloses a monolithic column with fixed monomeric avidin for enriching and identifying biotinylated species, which comprises a stationary phase made of a monolithic material containing a reactive group, and avidin is bound to it, monomerized and renatured.
[0006] At present, when facing the separation of biological macromolecules, especially when facing the enrichment and separation of nucleic acid substances from mixed materials including proteins and nucleic acids, the monolithic column needs to further improve the specific adsorption of biological macromolecules on the basis of general excellent adsorption performance, uniform results, low operating pressure and high flow rate. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the existing technology that the monolithic column is not optimized for biomacromolecules, especially nucleic acid substances, so the yield is low (generally 60%-80%), the stability is poor, the linear amplification reproducibility is inconsistent, and the optimization and control of the purification process are complex. In addition, the temperature control of the curing molding process is complex, the curing cycle is long, etc., resulting in high costs. An epoxy resin-based monolithic column material with specific adsorption capacity for nucleic acids is proposed, which retains the characteristics of excellent adsorption performance, uniform results, low operating pressure, and high flow rate of the epoxy resin monolithic column material, and also has excellent specific enrichment ability for nucleic acid substances.
[0008] To achieve the above objectives, the present invention proposes the following technical solutions.
[0009] The first aspect of the present invention provides an integral column.
[0010] A monolithic column has primary, secondary or tertiary amine groups grafted onto the inner surfaces of the pores and channels.
[0011] In some embodiments, the primary, secondary or tertiary amine groups are in the form of EP-OCH2CH(OH)CH-NR 1 R 2 of Form exists.
[0012] in:
[0013] EP is epoxy resin;
[0014] R 1 , R 2 is hydrogen, alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group; wherein alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group are optionally substituted by amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
[0015] The alkyl group is preferably a methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 1-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl and 3,3-dimethyl-2-butyl group.
[0016] The alkenyl group is preferably vinyl, prop-1-enyl, prop-2-enyl, 2-methylprop-1-enyl, but-1-enyl, but-2-enyl, but-3-enyl, butane-1,3-dienyl, 2-methylbut-1,3-dienyl, hex-1-enyl, hex-2-enyl, hex-3-enyl, hex-4-enyl, and hexa-1,3-dienyl groups.
[0017] The alkynyl groups are preferably ethynyl, 1-propynyl, 2-propynyl (propargyl), 1-butynyl, 2-butynyl, and 3-butynyl groups.
[0018] The cycloalkyl group is preferably a cyclopropyl, cyclobutyl, cyclopentyl, 1-cyclopent-1-enyl, 1-cyclopent-2-enyl, 1-cyclopent-3-enyl, cyclohexyl, 1-cyclohex-1-enyl, 1-cyclohex-2-enyl, 1-cyclohex-3-enyl, cyclohexadienyl, cycloheptyl, cyclooctyl group.
[0019] The heterocycloalkyl group is preferably a pyrrolidinyl, imidazolidinone, pyrazolidinyl, piperidinyl, 2,5-piperazinyl, pyranyl, morpholinyl group.
[0020] The poly(alkylene oxide) group is preferably a polyethylene glycol group, a polypropylene glycol group, or a polybutylene glycol group, and the terminal group is preferably a hydroxyl group or an amino group. The molecular weight is preferably 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, and preferably 3000.
[0021] The poly(alkyleneamine) group is preferably polyethylenediamine, polypropylenediamine, or polybutylenediamine, and the terminal group is preferably hydroxyl, amino, or C 1-6 The substituted amine group preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0022] The polyvinyl alcohol group is preferably a polyvinyl alcohol whose end or middle part is connected to EP-OCH2CH(OH)CH-N, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0023] The polyvinylamine group is preferably connected to EP-OCH2CH(OH)CH-N at the end or middle of polyvinyl alcohol, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0024] In some embodiments, the EP-OCH2CH(OH)CH-NR 1 R 2 The anion exchange capacity of the epoxy resin in the form of 30μmol / mL-300μmol / mL is 30μmol / mL, preferably 40μmol / mL, 50μmol / mL, 60μmol / mL, 70μmol / mL, 80μmol / mL, 90μmol / mL, 100μmol / mL, 110μmol / mL, 120μmol / mL, 130μmol / mL, 140μmol / mL, 150μmol / mL, 160μmol / mL, 170μmol / mL, 180μmol / mL, 190μmol / mL, 200μmol / mL, 210μmol / mL, 220μmol / mL, 230μmol / mL, 240μmol / mL, 250μmol / mL, 260μmol / mL, 270μmol / mL, 280μmol / mL, 290μmol / mL.
[0025] In some embodiments, the pore size of the monolithic column is 2 μm-6 μm, preferably 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6. .8μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9 μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm.
[0026] In some embodiments, the pore volume of the integral column is 1.1 mL / g-1.8 mL / g, preferably 1.10 mL / g, 1.15 mL / g, 1.20 mL / g, 1.25 mL / g, 1.30 mL / g, 1.35 mL / g, 1.40 mL / g, 1.45 mL / g, 1.50 mL / g, 1.55 mL / g, 1.60 mL / g, 1.65 mL / g, 1.70 mL / g, 1.75 mL / g, 1.80 mL / g.
[0027] In some embodiments, the porosity of the integral column is 55%-68%, preferably 55.0%, 55.5%, 56.0%, 56.5%, 57.0%, 57.5%, 58.0%, 58.5%, 59.0%, 59.5%, 60.0%, 60.5%, 61.0%, 61.5%, 62.0%, 62.5%, 63.0%, 63.5%, 64.0%, 64.5%, 65.0%, 65.5%, 66.0%, 66.5%, 67.0%, 67.5%, 68.0%.
[0028] In some embodiments, the raw material of the monolithic column includes a substance A containing multiple epoxy groups.
[0029] The substance containing multiple epoxy groups refers to a substance containing two or more epoxy groups in its structure.
[0030] In some embodiments, the substance containing multiple epoxy groups is preferably a polyepoxy glycidyl ether substance, or a polyepoxy glycidyl ester substance.
[0031] In some embodiments, the glycidyl ether substance may be one or more monomers satisfying the following structural formula I:
[0032]
[0033] In structural formula Ⅰ, R 1 is selected from hydrogen atom, substituted or unsubstituted C1-C 10 An alkyl group, or an epoxy group;
[0034] n is a positive integer from 0 to 10;
[0035] L 1 is selected from an oxygen atom or a nitrogen atom;
[0036] L 2 is selected from an oxygen atom or a nitrogen atom;
[0037] X is selected from substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C3-C 10 The cycloalkylene group,
[0038] Or, a benzene ring.
[0039] Preferably, the glycidyl ether substance is one or more of the following monomers (a)-(m);
[0040]
[0041] The above structure (a) is the structure of glycerol triglycidyl ether.
[0042] The above structure (b) is the structure of pentaerythritol tetraglycidyl ether.
[0043] The above structure (j) is the structure of 1,4-butanediol diglycidyl ether.
[0044] The above structure (k) is the structure of trimethylolethane triglycidyl ether.
[0045] The above structure (1) is the structure of bisphenol A diglycidyl ether.
[0046] The above structure (m) is the structure of bisphenol F diglycidyl ether.
[0047] In some embodiments, the glycidyl ether material may be one or more polymers satisfying the following structural formula II:
[0048]
[0049] In structural formula II, R 2 is selected from hydrogen atom, substituted or unsubstituted C1-C 10 Alkyl, or
[0050] m is a positive integer from 2 to 40.
[0051] Preferably, the glycidyl ether substance is one or more of the following polymers (1)-(4);
[0052]
[0053] In some embodiments, the glycidyl ester substance may be one or more monomers satisfying the following structural formula III;
[0054]
[0055] In formula III, Y is selected from substituted or unsubstituted C1-C 10 Alkylene, substituted or unsubstituted C3-C 10 A cycloalkylene ring, or a benzene ring.
[0056] Preferably, the glycidyl ester substance is the following monomer (A) and / or (B);
[0057]
[0058] In some embodiments, the substance containing multiple epoxy groups is preferably one or more of the following monomers (I)-(IV);
[0059]
[0060] In some embodiments, the substance containing multiple epoxy groups is preferably a polyepoxy glycidyl ether monomer and / or a polyepoxy glycidyl ether polymer.
[0061] Wherein, the polyepoxy group glycidyl ether monomer may be glycerol triglycidyl ether and / or pentaerythritol tetraglycidyl ether.
[0062] Wherein, the polyepoxy glycidyl ether polymer may be polyglycerol glycidyl ether and / or polypentaerythritol tetraglycidyl ether.
[0063] In some embodiments, when the substance containing polyepoxy groups is a mixture of the polyepoxy glycidyl ether monomer and the polyepoxy glycidyl ether polymer, the mixed volume ratio of the polyepoxy glycidyl ether monomer and the polyepoxy glycidyl ether polymer may be (0.1-9):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1. For example, a mixture of polyglycerol triglycidyl ether: pentaerythritol tetraglycidyl ether = 1:1, or polypentaerythritol tetraglycidyl ether: glycerol triglycidyl ether = 1:1.
[0064] In some embodiments, the molecular weight of the substance containing multiple epoxy groups may be 300-2000, such as a molecular weight of 550, a molecular weight of 700, a molecular weight of 1000, a molecular weight of 1200, a molecular weight of 1500, or a molecular weight of 1800.
[0065] In some embodiments, the raw material A may further include a substance containing a monoepoxy group. The substance containing a monoepoxy group refers to a substance containing one epoxy group in its structure.
[0066] The substance containing a monoepoxy group is preferably a monoepoxy glycidyl ether substance, or a monoepoxy glycidyl ester substance.
[0067] The monoepoxy glycidyl ether substance may be a substance having a conventional structure containing one epoxy group in the art, preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0068] The monoepoxy glycidyl ester substance may be one or more of phenyl glycidyl ether, butyl glycidyl ether, amyl glycidyl ether, octyl glycidyl ether, octadecyl glycidyl ether and naphthyl glycidyl ether, preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0069] In some embodiments, the raw material of the monolithic column includes porogen B.
[0070] In some embodiments, the porogen B is a solvent that is miscible with the substance A containing multiple epoxy groups and does not undergo polycondensation, preferably one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether, more preferably one or more of toluene, dioxane and methyl tert-butyl ether, such as toluene and dioxane, toluene and methyl tert-butyl ether, or dioxane and methyl tert-butyl ether.
[0071] In some embodiments, when the porogen B is a mixture of two different substances, the volume ratio of the two different substances may be (0.1-9):1, such as 0.5:1, 1:1, 2:1, 3:1, 5:1 or 7:1.
[0072] In some embodiments, the weight of the raw material A is preferably 22%-70%, such as 25%, 30%, 35%, 40%, 45%, 50%, 55%, 58%, 65% or 68% of the total weight of the raw material A and the porogen B. The weight of the porogen B is preferably 35%-80%, such as 40%, 45%, 50%, 60%, 65%, 70%, 75% or 78% of the total weight of the raw material A and the porogen B.
[0073] In some embodiments, the raw material A is a polyepoxy glycidyl ether monomer and / or a polyepoxy glycidyl ether polymer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether.
[0074] In some embodiments, the raw material A is a polyepoxy glycidyl ether polymer and a monoepoxy glycidyl ether monomer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether.
[0075] In some embodiments, the raw material A is polypropylene triglycidyl ether and a monoepoxy glycidyl ether monomer; the porogen B is one or more of toluene, xylene, dichloromethane, dichloroethane, dioxane, formamide (DMF), dimethyl sulfoxide (DMSO) and methyl tert-butyl ether; the monoepoxy glycidyl ether monomer is preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0076] In some embodiments, the raw material A is polypropylene triglycidyl ether and monoepoxy glycidyl ether monomers; the porogen B is one or more of toluene, dioxane and methyl tert-butyl glyceryl ether; the monoepoxy glycidyl ether monomer is preferably phenyl glycidyl ether and / or butyl glycidyl ether.
[0077] In some embodiments, the raw material of the monolithic column includes catalyst C.
[0078] In some embodiments, the catalyst C may be a Lewis acid and / or a Lewis acid complex.
[0079] The Lewis acid may be one or more of aluminum trichloride, boron trifluoride, ferric bromide, ferric chloride, zinc chloride, niobium trichloride pentachloride and sulfur trioxide, such as boron trifluoride.
[0080] The Lewis acid complex may be one or more of boron trifluoride ethyl ether, boron trifluoride acetonitrile, boron trifluoride dimethyl carbonate and boron trifluoride ethylamine.
[0081] In some embodiments, the weight of the catalyst C is preferably 0.3‰-1‰, such as 0.4‰, 0.5‰, 0.6‰, 0.7‰, 0.8‰ or 0.9‰, based on the total weight of the raw material A and the porogen B.
[0082] In some embodiments, the raw material of the monolithic column includes a weak anionic modifier D.
[0083] In some embodiments, the weak anionic modifier D has NHR 1 R 2 exists in the form of.
[0084] Among them, R 1 , R 2 is hydrogen, alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group; wherein alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group are optionally substituted by amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
[0085] The alkyl group is preferably a methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 1-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl and 3,3-dimethyl-2-butyl group.
[0086] The alkenyl group is preferably vinyl, prop-1-enyl, prop-2-enyl, 2-methylprop-1-enyl, but-1-enyl, but-2-enyl, but-3-enyl, butane-1,3-dienyl, 2-methylbut-1,3-dienyl, hex-1-enyl, hex-2-enyl, hex-3-enyl, hex-4-enyl, and hexa-1,3-dienyl groups.
[0087] The alkynyl groups are preferably ethynyl, 1-propynyl, 2-propynyl (propargyl), 1-butynyl, 2-butynyl, and 3-butynyl groups.
[0088] The cycloalkyl group is preferably a cyclopropyl, cyclobutyl, cyclopentyl, 1-cyclopent-1-enyl, 1-cyclopent-2-enyl, 1-cyclopent-3-enyl, cyclohexyl, 1-cyclohex-1-enyl, 1-cyclohex-2-enyl, 1-cyclohex-3-enyl, cyclohexadienyl, cycloheptyl, cyclooctyl group.
[0089] The heterocycloalkyl group is preferably a pyrrolidinyl, imidazolidinone, pyrazolidinyl, piperidinyl, 2,5-piperazinyl, pyranyl, morpholinyl group.
[0090] The poly(alkylene oxide) group is preferably a polyethylene glycol group, a polypropylene glycol group, or a polybutylene glycol group, and the terminal group is preferably a hydroxyl group or an amino group. The molecular weight is preferably 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, and preferably 3000.
[0091] The poly(alkyleneamine) group is preferably polyethylenediamine, polypropylenediamine, or polybutylenediamine, and the terminal group is preferably hydroxyl, amino, or C 1-6 The substituted amine group preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0092] The polyvinyl alcohol group is preferably connected to NH at the end or middle of polyvinyl alcohol, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0093] The polyvinylamine group is preferably connected to NH at the end or middle of polyvinyl alcohol, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
[0094] The second aspect of the present invention provides a method for preparing a monolithic column.
[0095] The preparation method comprises the following steps:
[0096] S1. Hydroxylating the monolithic column;
[0097] S2. epoxidizing the hydroxylated monolithic column;
[0098] S3. Modify the epoxidized monolithic column with weak anions.
[0099] Wherein in step S1, hydroxylation comprises the following steps:
[0100] S11. Cleaning the monolithic column;
[0101] S12. Drying the monolithic column;
[0102] S13. Hydroxylated monolithic column;
[0103] S14. Post-processing.
[0104] In the step S11, a piece of the monolithic column is taken and eluted with deionized water with a volume of 10-20 times to remove the protective solution.
[0105] In step S12, the monolithic column is drained with a vacuum pump. The draining time is 10-120 min, preferably 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min. The draining temperature is 5-50°C, preferably 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C.
[0106] In the step S13, an acidic aqueous solution is added into the dried monolithic column, and the temperature is raised to react, so that the residual epoxy groups in the monolithic column are converted into hydroxyl groups.
[0107] The acid in the acidic aqueous solution is sulfuric acid, hydrochloric acid, nitric acid, formic acid, or acetic acid. The concentration of the acid in the acidic aqueous solution is 0.1-0.5M, preferably 0.2M, 0.3M, or 0.4M.
[0108] The volume ratio of the acidic aqueous solution to the monolithic column is (3-30):1, preferably 5:1, 7:1, 10:1, 15:1, 20:1, 25:1, 30:1.
[0109] The temperature-raising reaction is to raise the temperature of the system to 40-80°C and react for 1-6 hours. The temperature is preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The reaction time is preferably 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h.
[0110] In the step S14, the hydroxylated monolithic column is rinsed with deionized water until the pH is neutral.
[0111] In some embodiments, after step S1, the epoxy group density of the whole column after hydroxylation is determined to be 0 or undetectable by epoxy group density measurement.
[0112] Wherein in step S2, epoxidation comprises the following steps:
[0113] S21. Cleaning the monolithic column;
[0114] S22. Drying the monolithic column;
[0115] S23. Epoxidized monolithic column;
[0116] S24. Post-processing.
[0117] In the step S21, a piece of the monolithic column is taken and eluted with deionized water with a volume of 10-20 times to remove the protective solution.
[0118] In step S22, the monolithic column is drained with a vacuum pump. The draining time is 10-120 min, preferably 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min. The draining temperature is 5-50°C, preferably 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C.
[0119] In the step S23, a solvent is added into the dried monolithic column, and epichlorohydrin is added after the column is fully soaked, and then a base is added, and the temperature is raised to react, so that the hydroxyl groups in the monolithic column are converted into epoxy groups.
[0120] The solvent is a DMSO:H2O mixed solvent, the ratio is 3:7-7:3, preferably 4:6, 5:5, 6:4. The volume ratio of the solvent to the monolithic column is (3-30):1, preferably 5:1, 7:1, 10:1, 15:1, 20:1, 25:1, 30:1.
[0121] The amount of epichlorohydrin added is 3-30% of the mass of the solvent, preferably 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%.
[0122] The alkali is one or more of sodium hydroxide, potassium hydroxide and ammonia water, and the added amount is 0.5-5% of the mass of the solvent, preferably 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0% and 4.5%.
[0123] The temperature-raising reaction is to raise the temperature of the system to 40-80°C and react for 1-8h. The temperature is preferably 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C. The reaction time is preferably 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h.
[0124] In the step S24, the epoxidized monolithic column is rinsed with ethanol and deionized water until the pH is neutral.
[0125] Wherein in step S3, the weak anion modification comprises the following steps:
[0126] S31. a mixed solvent and a weak anionic modifier D;
[0127] S32. The mixed solution of S31 is infiltrated into the monolithic column;
[0128] S33 weak anion modified monolithic column;
[0129] S34 post-processing.
[0130] In the step S31, the solvent is one or more of DMF, DMSO, and DMAc. The amount of the solvent added is 3-30% of the overall column, preferably 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%. The amount of the weak anion modifier D added is 10-50% (v / v) of the solvent, preferably 15%, 20%, 25%, 30%, 35%, 40%, 45%. The step S31 can also be mixed by vibration, ultrasound, etc.
[0131] In step S32, the epoxidized monolithic column prepared in step S2 is added to the mixed solution in step S31 to fully infiltrate the monolithic column. In step S32, vibration, ultrasound, vacuuming, etc. can also be used to assist in the infiltration.
[0132] In the step S33, the temperature is raised to allow the epoxy groups in the monolithic column to fully react with the weak anion modifier D.
[0133] The temperature-raising reaction is to raise the temperature of the system to 60-100° C. and react for 2-15 hours. The temperature is preferably 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C. The reaction time is preferably 2.0 h, 2.5 h, 3.0 h, 3.5 h, 4.0 h, 4.5 h, 5.0 h, 5.5 h, 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h, 8.5 h, 9.0 h, 9.5 h, 10.0 h, 10.5 h, 11.0 h, 11.5 h, 12.0 h, 12.5 h, 13.0 h, 13.5 h, 14.0 h, 14.5 h, 15.0 h.
[0134] In step S34, the monolithic column is cooled and taken out, and rinsed with ethanol and deionized water until the pH is neutral.
[0135] After step S34 is completed, in order to protect the monolithic column, it can be stored in a 20%-70% ethanol solution for standby use.
[0136] The third aspect of the present invention provides an application of a monolithic column for enrichment and separation of DNA or RNA.
[0137] The monolithic column has the function of specifically adsorbing DNA or RNA. Specifically, it can specifically adsorb DNA and / or RNA in a mixed solution containing biomacromolecules, so that the DNA and / or RNA can be enriched in the monolithic column and then eluted and separated.
[0138] A fourth aspect of the present invention is to provide a chromatographic column comprising the aforementioned monolithic column.
[0139] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0140] The reagents and raw materials used in the present invention are commercially available.
[0141] The positive and progressive effects of the present invention are:
[0142] 1. The monolithic column prepared by the present invention is rich in hydroxyl groups and has excellent compatibility with elution objects containing biological macromolecules, and is particularly suitable for the field of biological macromolecule chromatography.
[0143] 2. The monolithic column prepared by the present invention retains the characteristics of excellent adsorption performance, uniform results, low operating pressure and high flow rate of epoxy resin monolithic column materials. The pores are adjustable, submicron-micron level, relatively uniformly distributed, and present a single-peak normal distribution, with high ligand utilization. The pores are through holes, without diffusion effect, no need to increase retention time, shorten process cycle, no obvious eddy current phenomenon, low shear force, no effect on sample load at high flow rate, and high toughness.
[0144] 3. The monolithic column prepared by the present invention has excellent specific adsorption capacity for nucleic acid substances and is suitable for the enrichment and separation of DNA and / or RNA substances. BRIEF DESCRIPTION OF THE DRAWINGS
[0145] Figure 1 This is the pore size distribution diagram of the integral column block prepared in Example 8.
[0146] Figure 2 This is the pore size distribution diagram of the integral column block prepared in Comparative Example 3.
[0147] Figure 3 This is the pore size distribution diagram of the integral column block prepared in Comparative Example 4.
[0148] Figure 4 This is a scanning electron microscope image of the integral column block prepared in Preparation Example 3.
[0149] Figure 5 This is a scanning electron microscope image of the integral column block prepared in Example 8.
[0150] Figure 6 This is a scanning electron microscope image of the integral column block prepared in Comparative Example 3.
[0151] Figure 7 This is a scanning electron microscope image of the integral column block prepared in Comparative Example 4.
[0152] Figure 8 This is a chromatography experiment diagram of the integral column block prepared in Example 7. DETAILED DESCRIPTION
[0153] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0154] Unless otherwise specified, the reagents used in the following examples and comparative examples are all conventional commercially available products in the art.
[0155] Preparation Example
[0156] S1. Hydroxylation: Take 1 mL of the monolithic column and wash it with deionized water for 20 times the volume on a sand core funnel to remove the protective liquid. Use a vacuum pump to drain the sand core funnel for 60 minutes at an ambient temperature of 25°C.
[0157] The 1 ml monolithic column block after being drained was transferred to a glass reaction bottle, and a 0.2 M deionized sulfuric acid solution was added, with the amount added being 10 ml of reaction solution / block (1 mL); ultrasonication was performed for 30 min to accelerate the rapid immersion of the reaction solution into the monolithic column block; after the ultrasonication, the glass reaction bottle was transferred to a water bath, heated to 60°C, and kept warm for 4 h; the hydroxylated monolithic column block was placed on a sand core funnel and rinsed with deionized water until the pH was neutral (6.5-7).
[0158] Through the epoxy group density measurement, it was determined that the block epoxy group density after hydroxylation was 0;
[0159] S2. Epoxidation: Take 1 mL of the hydroxylated monolithic column block, elute 20 times the volume of deionized water on a sand core funnel, and drain it on the sand core funnel with a vacuum pump for 60 minutes at an ambient temperature of 25°C.
[0160] After draining, transfer 1mL of the monolithic column block to a glass reaction bottle, first add solvent (50% DMSO deionized water solution), the amount added is 10mL / block (1mL); ultrasonic for 20 minutes to fully soak the monolithic column block; then add epichlorohydrin, the amount added is 10% of the solvent mass, and continue ultrasonic for 30 minutes; finally add 2% sodium hydroxide, continue ultrasonic for 10 minutes, control the temperature at 20℃, and mix thoroughly. Move to a constant temperature water bath at 60℃, react for 6 hours; alternately rinse with ethanol and water for 20 times the volume of each block; vacuum dry after washing, dry and store at low temperature.
[0161] Table 1 Performance of Epoxidized Monolithic Column Block Preparation Example
[0162]
[0163] The average pore size of the samples 1 to 4 increases gradually through the determination of epoxy group density. After hydroxylation and then epoxidation, the epoxy group density decreases as the pore size increases.
[0164] Comparative Examples 1 and 2 are prepared by directly performing epoxidation treatment on Example 1 and Example 4 without hydroxylation, and the ligand density is significantly less than the value after epoxidation after the above hydroxylation. This indicates that a small amount of epoxy groups remain after the integral column is formed, and the epoxy groups in the original integral column are also converted into hydroxyl groups by hydroxylation. Together with the hydroxyl groups existing in the original integral column, they are used as reactants and converted into epoxy groups in the subsequent epoxidation step, thereby increasing the density of epoxy groups in the integral column. In addition, after hydroxylation and epoxidation, the flexibility of the epoxy groups increases, and there is a C3 connecting group between the epoxy groups and the integral column substrate, which enables the specifically adsorbed groups to extend from the substrate surface, thereby improving the capture capacity.
[0165] Example
[0166] Add DMF solvent to the reaction bottle, the amount added is 10mL / piece (1mL). Then add liquid A as shown in the table below, the amount added is 30% of the solvent mass. After the two are fully mixed, ultrasonicate for 10 minutes.
[0167] Add the epoxidized monolithic column block prepared in the preparation example to the above reaction solution, ultrasonicate or vacuumize for 10 minutes to fully infiltrate; move the above reaction bottle to a 60°C oil bath, heat and react for 2 hours; then raise the temperature to 80°C and react for 10 hours; cool down, take out the monolithic column block that has reacted, and wash it twice with ethanol and water alternately, with the washing volume being 20 times the block volume, and wash until the pH of the washing water solution is 6.5-7. Finally, store the monolithic column in 20%-70% ethanol for later use.
[0168] Table 2 Examples and Comparative Examples
[0169]
[0170]
[0171] Effect test pore size distribution, pore volume, porosity determination
[0172] Test method: Mercury intrusion method
[0173] Test equipment: USA-McMerrittick-autoporeV 9620
[0174] Test results:
[0175] Example 1-6 shows that after the monolithic column block with an average pore size of 2.7 μm was modified with amino epoxy, the pore size, pore volume and porosity parameters did not change significantly;
[0176] In Example 7-12, after the monolithic column block with an average pore size of 4.2 μm was modified with amino epoxy, the pore size, pore volume and porosity parameters did not change significantly;
[0177] In Examples 13-18, after the monolithic column blocks with an average pore size of 5.2 μm were modified with amino epoxy, the pore size, pore volume and porosity parameters did not change significantly;
[0178] In Comparative Examples 1-4, the pore size changes significantly and gradually decreases, indicating that when the reaction temperature is increased or the amount of polyethyleneimine is increased, the pore size is significantly affected. The influence of the modification reaction on the pore structure of the overall column block can be avoided by controlling the temperature and amount. The pore size of Comparative Examples 1-3 is reduced from the original 4.2μm to 1.73μm, 0.56μm, and 0.15μm, respectively. The pore structure of Comparative Example 4 is abnormal, and most of the pores may be completely destroyed or blocked.
[0179] Table 3 Pore size distribution, pore volume, porosity test results
[0180]
[0181]
[0182] Figure 1 This is the pore size distribution diagram of Example 8, Figure 2 This is the pore size distribution diagram of Comparative Example 3, Figure 3 This is the pore size distribution diagram of comparative example 4. It can be seen intuitively that after the excessive high temperature reaction of polyethyleneimine 5000, the pore size distribution becomes wider and the pore size becomes significantly smaller. The pore size distribution in comparative example 4 is abnormal, and there is no normal distribution curve. It is speculated that the pore size structure is basically destroyed and blocked. Only the remaining pores of different sizes are
[0183] Field emission electron microscope scanning test
[0184] Test objects: Preparation Example 3, Example 8, Comparative Example 3, Comparative Example 4
[0185] Test equipment: Germany-Zeiss sigma300, Oxford spectroscopy.
[0186] Test results:
[0187] Figure 4 To prepare the electron microscope image of Example 3; Figure 5 This is the electron microscope image of Example 8; Figure 6 This is the electron microscope image of comparative example 3; Figure 7This is the electron microscopy image of comparative example 4. According to the electron microscopy results, it can be intuitively concluded that the pore sizes of comparative examples 3 and 4 are significantly smaller, and it can be seen that many pore gaps are completely blocked. The results are consistent with the pore size distribution, pore volume, and porosity test results of the aforementioned mercury intrusion method test.
[0188] Epoxy ligand density determination
[0189] Test objects: Preparation examples 1-4 and comparative examples 1-2 in Table 1
[0190] Test method: Sodium thiosulfate-hydrochloric acid titration method.
[0191] The chromatographic materials of Preparation Examples 1-4 and Comparative Examples 1-2 modified by epoxy were cleaned with deionized water, placed in a sand core funnel and vacuum-dried for 10 minutes, and then weighed 1 piece (about 0.5g) and placed in a ground-mouth conical flask, 3mL, 1.3mol / L sodium thiosulfate and 1-2 drops of phenolphthalein indicator were added, and the conical flask was sealed and placed at room temperature for 1 hour. The supernatant solution after the reaction was titrated with 0.1mol / L hydrochloric acid standard solution until the red solution became colorless. Substitute the consumed volume of hydrochloric acid standard solution into the following formula to calculate the epoxy ligand density:
[0192] S=1000*[M HCl (V0-V1)*ρ / W]
[0193] S: epoxy ligand density, μmoL / mL;
[0194] M HCl : Hydrochloric acid concentration, mmoL / mL;
[0195] V0, V1: volume of HCl before and after titration, mL;
[0196] ρ: medium density (1.2 g / mL);
[0197] W: The mass of the whole block weighed (g).
[0198] Test equipment: acid-base titration device.
[0199] Test results: See Table 1.
[0200] Anion exchange capacity determination test object: anion exchange monolithic columns prepared in Examples 1-18 and Comparative Examples 1-4 in Table 2 above.
[0201] Determination method: GB 5760-86.
[0202] Test equipment: acid-base titration device.
[0203] Test results: as shown in Table 4 below.
[0204] Table 4 Anion exchange capacity results of each embodiment and comparative example
[0205]
[0206]
[0207] Plasmid DNA enrichment test of bacterial lysate
[0208] Test objects: Examples 1-18 and Comparative Examples 1-3
[0209] Test method: as follows
[0210] 1. Preparation of bacterial lysate:
[0211] 1.1. Bacterial strain amplification culture, bacterial strain (Escherichia coli TOP10, pET-30a-rspa, about 6500bp). (Bacterial strain amplification is a routine operation in the field of bioengineering and will not be described in detail here);
[0212] 1.2. Alkaline lysis of the cells: the cells after amplification and culture are centrifuged to collect the cell solids, and the crude plasmid is extracted by the classic three-step alkaline lysis method (this is a routine operation in the field of bioengineering and will not be described in detail here);
[0213] 1.3. Ammonium sulfate / calcium chloride precipitation method to remove RNA, generally the salt concentration is 0.3-2M calcium chloride or ammonium sulfate (this is a routine operation in the field of bioengineering and will not be described in detail here);
[0214] 1.4. Collect the supernatant by centrifugation, which is the crude product before plasmid loading;
[0215] 2. Column chromatography test of lysate:
[0216] 2.1 Place the reacted weak anion exchange chromatography stack (DEAE-Plus) in a 1 mL radial flow chromatography tool (Yuji Bio-Chromatography Tool);
[0217] 2.2. Connect the chromatography tool containing the DEAE-Plus block to the liquid chromatography equipment, use the balancing solution W: 50mMTris-HCl+10mM EDTA, pH7.2-7.4, balance 5-10 times the volume of the column until the conductivity, pH, and UV baselines are stable;
[0218] 2.3. Take the crude plasmid (pET-30a-rspa, 6500bp), dilute with balance to conductivity ≤30ms / cm, inject 150mL through the chromatography equipment injection system, flow rate 5mL / min; use (5%-25% eluent E + 75%-95% balance solution W to wash impurities)
[0219] 2.4 Use eluent E (50mM Tris-HCl+10mM EDTA+2M NaCl, PH7.2-7.4) for gradient elution to collect plasmid DNA at a flow rate of 2-3mL / min; collect eluent samples for micro-ultraviolet spectrophotometry and agarose gel electrophoresis determination
[0220] 2.5. Regeneration: First, use 100% eluent to regenerate the chromatographic stack (DEAE-Plus) column at a flow rate of 2-3 mL / min; then use 1M sodium hydroxide to wash the column, and immediately wash the column with deionized water until it is neutral.
[0221] Chromatography test results: See Table 5 below:
[0222] Table 5 Chromatography test results
[0223]
[0224]
[0225]
[0226] It can be clearly seen from Table 5 that the purity of the crude plasmid is significantly increased after enrichment by the monolithic column (when OD260 / 280 < 1.8, it indicates contamination by impurities such as protein, when OD260 / 280 > 2, it indicates contamination by small nucleic acid RNA in the plasmid sample, and when 1.8 ≤ OD260 / 280 ≤ 2, the plasmid purity is relatively pure and can be used for subsequent experiments); and the concentration of the plasmid recovered by the eluent E is significantly higher than the original concentration; the OD260 / 280 ratio of the plasmid purity of the eluted E is between 1.8 and 1.96.
[0227] The ratio of eluent E is proportional to the salt concentration in the eluent. From the results, it can be seen that 3-diethylaminopropylamine, diethylamine and hexamethylenediamine can recover plasmids at lower salt concentrations, and polyethyleneimine 5000 requires a higher salt concentration for elution, which may be due to the steric hindrance of the polymer ligand and the complex amine, so that it requires a higher ionic strength to elute the plasmid; and the larger the pore size, the easier it is to elute, the smaller the elution volume, and the higher the elution concentration. Overall, the plasmid DNA of 6500bp in Examples 1-18 can basically be well recovered, basically around 1.5mg.
[0228] The pore size of Comparative Examples 1-3 becomes smaller, but Comparative Example 1 can also achieve the recovery of about 1.5 mg of plasmid at 6500 bp plasmid DNA, while Comparative Examples 2-3 recover about 1 mg and 0.8 mg of plasmid respectively. In addition, the elution volume of Comparative Examples 1-3 gradually increases, the proportion of eluent E gradually increases, and the yield decreases, which is related to the smaller pore size and the damage and blockage of the channel.
[0229] Figure 8 The chromatogram of Example 7, FT is the injection flow peak, mainly some amino acids, proteins, pigments, fatty acids and other small molecule metabolites impurities in the E. coli lysate, W is mainly eluted residual RNA and some protein impurities, and E is the eluted enriched plasmid part. It can be seen intuitively from the chromatogram that the peak shape is good, the elution peak is in a standard normal distribution, and the elution peak has no obvious tailing phenomenon, and the maximum value of the FT flow peak is basically stable at 750mAU, proving that the plasmid DNA has not penetrated.
[0230] 15000bp large plasmid loading and yield test
[0231] Test objects: Examples 4, 10, and 16
[0232] Test method: as follows
[0233] 3.1. Anion exchange chromatography stacks (DEAE-Plus) were placed in 1 mL radial flow chromatography tooling (Yuji Bio-Chromatography Tooling, utility model patent);
[0234] 3.2. Connect the chromatography tool containing the DEAE-Plus block to the liquid chromatography equipment, use the balancing solution: 50mMTris-HCl+10mM EDTA, pH7.2-7.4, balance 5-10 times the volume of the column until the conductivity, pH, and UV baselines are stable;
[0235] 3.3. Take a plasmid sample (pHelper-CA plasmid DNA (about 15000bp, provided by Kaituo Biotechnology), this sample is pure, only the binding and elution efficiency performance of super large plasmids are investigated), dilute it to 1mg / mL with a balance, and inject 5mg through the chromatography equipment injection system at a flow rate of 5mL / min;
[0236] 3.4 Use eluent E (50mM Tris-HCl+10mM EDTA+2M NaCl, PH7.2-7.4) for gradient elution, using 75% eluent + 25% balance solution to elute the target substance, with a flow rate of 2-3mL / min;
[0237] 3.5. Regeneration: First, use 100% eluent to regenerate the chromatographic stack (DEAE-Plus) column at a flow rate of 2-3 mL / min; then use 1M sodium hydroxide to wash the column, and immediately wash the column with deionized water until it is neutral.
[0238] Test results: See Table 6
[0239] Table 6 15000bp large plasmid loading and yield test results
[0240]
[0241]
[0242] It can be clearly concluded from the results in Table 6 that in terms of the yield of super-large plasmid DNA (15000 bp), the larger the pore size of the monolithic column, the higher the yield. The 5.2 μm weak anion exchange chromatography monolithic column has the advantages of specific enrichment and separation in the chromatographic purification of super-large plasmid DNA.
Claims
1. A monolithic column, characterized in that: The pores and inner surfaces of the channels in the monolithic column are grafted with primary amine groups, secondary amine groups or tertiary amine groups.
2. The integral column according to claim 1, characterized in that: The primary amine group, secondary amine group or tertiary amine group exists in the form of EP-OCH2CH(OH)CH-NR1R2; in: EP is epoxy resin; R 1 , R 2 is hydrogen, alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group; wherein alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group are optionally substituted by amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
3. The integral column according to claim 2, characterized in that: The alkyl group is preferably a methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 1-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl and 3,3-dimethyl-2-butyl group; The alkenyl group is preferably vinyl, prop-1-enyl, prop-2-enyl, 2-methylprop-1-enyl, but-1-enyl, but-2-enyl, but-3-enyl, butane-1,3-dienyl, 2-methylbut-1,3-dienyl, hex-1-enyl, hex-2-enyl, hex-3-enyl, hex-4-enyl, and hexa-1,3-dienyl groups; The alkynyl group is preferably ethynyl, 1-propynyl, 2-propynyl (propargyl), 1-butynyl, 2-butynyl, and 3-butynyl groups; The cycloalkyl group is preferably a cyclopropyl, cyclobutyl, cyclopentyl, 1-cyclopent-1-enyl, 1-cyclopent-2-enyl, 1-cyclopent-3-enyl, cyclohexyl, 1-cyclohex-1-enyl, 1-cyclohex-2-enyl, 1-cyclohex-3-enyl, cyclohexadienyl, cycloheptyl, cyclooctyl group; The heterocycloalkyl group is preferably a pyrrolidinyl, imidazolidinone, pyrazolidinyl, piperidinyl, 2,5-piperazinyl, pyranyl, morpholinyl group; The poly(alkylene oxide) group is preferably a polyethylene glycol group, a polypropylene glycol group, or a polybutylene glycol group, preferably the terminal group is a hydroxyl group or an amino group, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000; The poly(alkyleneamine) group is preferably a polyethylenediamine group, a polypropylenediamine group, or a polybutylenediamine group, and the terminal group is preferably a hydroxyl group, an amino group, or a C 1-6 Substituted amine groups, preferably having a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000; The polyvinyl alcohol group is preferably a polyvinyl alcohol whose end or middle part is connected to EP-OCH2CH(OH)CH-N, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000; The polyvinylamine group is preferably connected to EP-OCH2CH(OH)CH-N at the end or middle of polyvinyl alcohol, and preferably has a molecular weight of 500-5000, preferably 1000-5000, preferably 2000-4000, preferably 2500-3500, preferably 3000.
4. The integral column according to any one of claims 1 to 3, characterized in that: The EP-OCH2CH(OH)CH-NR 1 R 2 The anion exchange capacity of the epoxy resin in the form of is 30 μmol / mL-300 μmol / mL, preferably 40 μmol / mL, 50 μmol / mL, 60 μmol / mL, 70 μmol / mL, 80 μmol / mL, 90 μmol / mL, 100 μmol / mL, 110 μmol / mL, 120 μmol / mL, 130 μmol / mL, 140 μmol / mL, 150 μmol / mL, 160 μmol / mL, 170 μmol / mL, 180 μmol / mL, 190 μmol / mL, 200 μmol / mL, 210 μmol / mL, 220 μmol / mL, 230 μmol / mL, 240 μmol / mL, 250 μmol / mL, 260 μmol / mL, 270 μmol / mL, 280 μmol / mL, 290 μmol / mL; The pore size of the monolithic column is 2 μm-6 μm, preferably 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm , 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm , 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm, 5.6μm, 5.7μm, 5.8μm, 5.9μm, 6.0μm; The pore volume of the monolithic column is 1.1 mL / g-1.8 mL / g, preferably 1.10 mL / g, 1.15 mL / g, 1.20 mL / g, 1.25 mL / g, 1.30 mL / g, 1.35 mL / g, 1.40 mL / g, 1.45 mL / g, 1.50 mL / g, 1.55 mL / g, 1.60 mL / g, 1.65 mL / g, 1.70 mL / g, 1.75 mL / g, 1.80 mL / g; The porosity of the integral column is 55%-68%, preferably 55.0%, 55.5%, 56.0%, 56.5%, 57.0%, 57.5%, 58.0%, 58.5%, 59.0%, 59.5%, 60.0%, 60.5%, 61.0%, 61.5%, 62.0%, 62.5%, 63.0%, 63.5%, 64.0%, 64.5%, 65.0%, 65.5%, 66.0%, 66.5%, 67.0%, 67.5%, 68.0%.
5. The integral column according to any one of claims 1 to 4, characterized in that: The raw materials of the monolithic column include a substance A containing multiple epoxy groups, a porogen B, and a weak anion modifier D; The weak anionic modifier D has NHR 1 R 2 exists in the form of; Among them, R 1 , R 2 is hydrogen, alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group; wherein alkyl, alkenyl, alkynyl, cycloalkyl, heterocycloalkyl, poly(alkylene oxide) group, poly(alkylene amine) group, polyvinyl alcohol group, polyvinyl amine group are optionally substituted by amino, hydroxyl, -C 1-6 Alkyl, -C 1-6 Hydroxyalkyl, -C 1-6 The aminoalkyl group is substituted or hybridized with O, N, Si, P, or S.
6. A method for preparing a monolithic column according to any one of claims 1 to 5, characterized in that: The steps include: S1. Hydroxylating the monolithic column; S2. epoxidizing the hydroxylated monolithic column; S3. Modify the epoxidized monolithic column with weak anions.
7. The preparation method according to claim 6, characterized in that: The step S1 comprises: S13. Add an acidic aqueous solution into the dried monolithic column and heat the reaction to convert the residual epoxy groups in the monolithic column into hydroxyl groups.
8. The preparation method according to any one of claims 6 to 7, characterized in that: The step S2 comprises: S23. Add solvent into the whole column, add epichlorohydrin after it is fully soaked, then add alkali, and heat the reaction to convert the hydroxyl groups in the whole column into epoxy groups.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The step S3 comprises: S32. The epoxidized monolithic column prepared in step S2 is added to the mixed solution of S31 to fully infiltrate the mixture; S33. Raise the temperature to allow the epoxy groups in the monolithic column to fully react with the weak anion modifier D.
10. Use of the monolithic column according to any one of claims 1 to 5 or the monolithic column prepared by the preparation method according to any one of claims 6 to 9 for enrichment and separation of DNA or RNA.
11. A chromatographic column, characterized in that: It comprises the monolithic column as described in any one of claims 1 to 5 or the monolithic column prepared by the preparation method as described in any one of claims 6 to 9.
Citation Information
Patent Citations
Hydrophilic integral material as well as preparation and application thereof
CN113145088A
Chromatographic material feedstock composition, chromatographic material and methods of making and using same, monolithic column and chromatography stack
CN118179462B
Monolithic column having immobilized monomeric avidin for enriching and identifying biotinylated species
EP2485836A1
Alkylamine silica gel capillary monolithic column and preparation method and use thereof
CN101306263A
Anion exchange integral material as well as conventional liquid phase chromatographic column or quartz capillary column taking anion exchange integral material as separating medium and preparation method thereof
CN102059157A
Cited By
Weak anion-modified monolithic column
WO2025232847A1